Grant's atlas of anatomy - Agur, A. M. R.; Dalley, Arthur F. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2009)
"The new edition of this classic anatomy atlas features many improvements, including updated artwork, more vital tissue colors, new conceptual diagrams, re-colored illustrations, and a more consistent art style. Clinical integration has been enhanced in this edition, with clinical material clearly highlighted for easy identification. In addition, the organization within each chapter has been updated to provide a clearer and more consistent approach."--BOOK JACKET.
Keywords: Human anatomy -- Atlases; Anatomy, Regional -- Atlases